The automated radiosynthesis and purification of the opioid receptor antagonist, [6‐O‐methyl‐11C]diprenorphine on the GE TRACERlab FXFE radiochemistry module. (1st April 2014) - Fairclough, Michael; Prenant, Christian; Brown, Gavin; McMahon, Adam; Lowe, Jonathan; Jones, Anthony
<x xml:space="preserve">Abstract</x> [6‐O‐Methyl‐11C]diprenorphine ([11C]diprenorphine) is a positron emission tomography ligand used to probe the endogenous opioid system in vivo. Diprenorphine acts as an antagonist at all of the opioid receptor subtypes, that is, μ (mu), κ (kappa) and δ (delta). The radiosynthesis of [11C]diprenorphine using [11C]methyl iodide produced via the 'wet' method on a home‐built automated radiosynthesis set‐up has been described previously. Here, we describe a modified synthetic method to [11C]diprenorphine performed using [11C]methyl iodide produced via the gas phase method on a GE TRACERlab FXFE radiochemistry module. Also described is the use of [11C]methyl triflate as the carbon‐11 methylating agent for the [11C]diprenorphine syntheses. [11C]Diprenorphine was produced to good manufacturing practice standards for use in a clinical setting. In comparison to previously reported [11C]diprenorphine radiosyntheisis, the method described herein gives a higher specific activity product which is advantageous for receptor occupancy studies. The radiochemical purity of [11C]diprenorphine is similar to what has been reported previously, although the radiochemical yield produced in the method described herein is reduced, an issue that is inherent in the gas phase radiosynthesis of [11C]methyl iodide. The yields of [11C]diprenorphine are nonetheless sufficient for clinical research applications. Other advantages of the method described herein are an improvement to both reproducibility and reliability of the production as well as simplification of the purification and formulation steps. We suggest that our automated radiochemistry route to [11C]diprenorphine should be the method of choice for routine [11C]diprenorphine productions for positron emission tomography studies, and the production process could easily be transferred to other radiochemistry modules such as the TRACERlab FX C pro. Copyright © 2014 John Wiley & Sons, Ltd.